Pemanfaatan Digitalisasi pada UMKM Haryani Batik Tulis dalam Penguatan Sektor Ekonomi di Desa Ambulu Kabupaten Jember - Ajeng Pramesthy Hardiani Kusuma; Attar Firman Adi Sukma (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
The increase in internet users based on the increasing need for the internet has led to an increase in the number of e-commerce users in Indonesia. The use of e-commerce for MSMEs can increase economic value, especially for MSMEs in Ambulu Village, which still use conventional methods. The potential for developing e-commerce in Ambulu Village is also supported by the large number of residents with the type of work as traders. Therefore, KKN Kolaboratif II in Ambulu Village is carried out in the form of outreach and assistance to MSMEs in Ambulu Village. The results of this activity are an understanding of the use of digital marketing materials for MSMEs with a percentage of 100%, creation of digital content with a percentage of 80%, and an interest in utilizing digitization into business units with a percentage of 100%.